Penyelenggaraan Perlindungan Perempuan dan Anak dalam Berbagai Bentuk Kekerasan di Provinsi Nusa Tenggara Barat Melalui Peraturan Daerah Nomor 8 Tahun 2015 - Wahyu Trisno Aji (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Basically humans are social beings who live side by side to complement one another. However, acts of violence are still in the midst of an understanding that social creatures are vulnerable to women and children. This article aims to analyze regional regulations (PERDA) No. 8 of 2015 concerning the implementation of protection for women and children against various types of violence that occur in the province of West Nusa Tenggara (NTB). The research method used in this study is a qualitative method and a normative approach. legal concept analysis approach (analytical and conceptual approach), and the fact approach, so that in this study the primary source was used, namely NTB regional regulation number 8 of 2015. The results of this research analysis are in regional regulation no 5 of 2015 explain the principles. Analysis, and the purpose of this regulation is made. There are also forms of protection. Prevention, and handling, recovery of victims of violence. This regional regulation explains the punishment given to perpetrators of violence against women and children, and also explains how the participation of the community, legal institutions, government agencies and other parties takes part in the implementation of the protection of women and children in the various forms of violence that occur.